Peran Gender dalam Pendidikan Islam - Putra, Aris Try Andreas (Jurnal Pendidikan Islam, 2014)
The issue of gender is an issue that often be discussed in all aspects of life, including Islamic education. The term of gender is not only for women, but also for men. In fact, women are in marginalized position, so this discussion is much more for woman autorities. On the other hand, men that are reputed as persons who have higher levels in several aspects of life. The marginalized position of women is expected to encourage mindset changes in various segments of social life. Gender is determined by several factors, created, and socialized, and implemented by means of social and religion. Islamic education in Indonesia is provided for all citizens. This article is as the explanation of the role of gender of Islamic education in Indonesia.